The animal cruelty-delinquency relationship: violence graduation, deviance generalization, or antecedent lifestyle? - Walters, Glenn D. (Animal abuse and interpersonal violence, 2024)
Several hypotheses have been advanced in an effort to explain the association that several decades of research suggests may exist between animal cruelty and delinquency. First, there is the violence graduation hypothesis, which holds that animal cruelty serves as a springboard to later interpersonal violence. Then, there is the deviance generalization hypothesis, which postulates that animal cruelty is part of a larger deviance syndrome. Finally, there is the antecedent lifestyle hypothesis, which maintains that animal cruelty and behaviors like bullying have their basis in a fearless temperament, callous/unemotional traits, and a proactive antisocial attitude. The antecedent lifestyle hypothesis further contends that in some cases delinquent behavior stems either directly or indirectly from one or more of the developmental antecedents identified by the hypothesis (i.e., animal cruelty, bullying, parental defiance, fire-setting, drug use, sexual promiscuity). In the first part of this chapter, the concurrent and predictive relationships that appear to connect animal cruelty to delinquency are explored, verified, and documented. In the second part of this chapter, the violence graduation, deviance generalization, and antecedent lifestyle hypotheses are evaluated against existing data in an effort to determine which hypothesis or set of hypotheses best explains the animal cruelty–delinquency relationship.